Airflow-restricting mask reduces acute performance in resistance exercise - Motoyama, Y. L.; Joel, G. B.; Pereira, P. E. A.; Esteves, G. J.; Azevedo, P. H. S. M. (Sports, 2016)
Background: The aim of this study was to compare the number of repetitions to volitional failure, the blood lactate concentration, and the perceived exertion to resistance training with and without an airflow-restricting mask. Methods: Eight participants participated in a randomized, counterbalanced, crossover study. Participants were assigned to an airflow-restricting mask group (MASK) or a control group (CONT) and completed five sets of chest presses and parallel squats until failure at 75% one-repetition-maximum test (1RM) with 60 s of rest between sets. Ratings of perceived exertion (RPEs), blood lactate concentrations (Lac-), and total repetitions were taken after the training session. Results: MASK total repetitions were lower than those of the CONT, and (Lac-) and MASK RPEs were higher than those of the CONT in both exercises. Conclusions: We conclude that an airflow-restricting mask in combination with resistance training increase perceptions of exertion and decrease muscular performance and lactate concentrations when compared to resistance training without this accessory. This evidence shows that the airflow-restricting mask may change the central nervous system and stop the exercise beforehand to prevent some biological damage